Analisis Perubahan Kecepatan dan Waktu Tempuh Sistem Robot Line Follower pada Lintasan yang Berbeda - syafaruddin Ch; Suthami Ariessaputra; Budi Darmawan; Paniran; Cahyo Mustiko Okta Muvianto (Depertment of Electrical Engineering University of Mataram, 2023)
A line follower robot is a robot that works along a line. This robot is a very simple type of robot, so it is often used as training material for students who are new to robots. One of the indicators for assessing the performance of a line follower robot is the travel time achieved by the line follower robot in covering various trajectories correctly. The average speed of the robot at 90% and 75% PWM settings is almost the same with a value of around 41 cm/second, while at 50% PWM settings it is much reduced to 35.63 cm/second. At the 90% PWM setting, it can be seen that the path length ratio is 4.32: 2.06: 1, while the travel time ratio is 4.44: 2.66: 1. At the 75% PWM setting, it can be seen that the path length ratio is 4.32: 2.06 : 1. while the travel time ratio is 4.38 : 2.41 : 1. At 50% PWM setting, it can be seen that the path length ratio is 4.32 : 2.06 : 1. while the travel time ratio is 4.09 : 2.09 : 1